Abruptio Placentae: Risk factors and Perinatal outcome - Jabeen, Musarrat; Gul, Fouzia (Journal of Postgraduate Medical Institute, 2011)
To determine the risk factors and maternal and fetal outcome of placental abruption. This study was conducted in the departmetn of Gynae / Obst PGMi LRH, Peshawar over a period of one year. Patients with abruption were confirmed by the presence of retrplacental clots of the depression of underlying placental tissues. all the details of the history physical examination of women, investigations and particularly details of delivery, baby and postpartum period recorded. Abruption placetae is common in women with advancing age, high parity, hypertensive disorders of pregnancy and smoking. Abruptio placentae is major risk factor for maternal and foetal morbidity and mortaltiy.